Pengaruh Motivasi Belajar Terhadap Keterampilan Menyimak Intensif Bahasa Inggris Siswa Kelas XI SMAN 15 Kota Bekasi - Nia Liska Saputri; Irfan Hadi (Peneliti.net, 2022)
The purpose of this study was to determine the effect of motivation on intensive English listening skills in class XI students of SMAN 15 Bekasi. Abstract and keywords are written in English. The number of respondents was 76 students. The method used is a quantitative method. The data will be tested for validity, reliability, motivation to contribute to intensive listening skills of 22.09% and the remaining contribution of 77.91% is the contribution of other factors not examined, secondly there is a strong positive relationship between the variables of Learning Motivation on intensive listening skills on the eye. English lessons for class XI SMAN 15